The optimization of machining cutting zone based on improved genetic algorithm. Issue 1 (June 2021) - Ji, S C; Lu, D X; Deng, L
Abstract: The processing accuracy in the machining cutting zone is uneven. The condition of processing parts is most sharply worsened, when the guides junction occurs opening (the graph of pressure in the guides' surfaces is not distributed over their entire length). The aim of this paper is optimization of the effective cutting zone (ECZ) of machining tool, in which graph of the guides pressure is always distributed on all surfaces. The layout of machining tools must ensure the largest zone of ECZ. The optimization of the objective function could change these parameters of layout, such as the vector of cutting forces, the weighting centre of the support, the coordinates of applied force from driving system, the width and length of guides. The task of optimization is a nonlinear extreme. According to the structural parameters of the machine tool, the pressure equation of the guide rail is established. For finding the optimal value, the method for determining extremum of the objective function used improving genetic algorithm (GA). Application of the method GA has allowed approximately ten times to raising the speed of determining of the layout parameters that ensure the largest ECZ.